Characterization and luminescence of Eu/Sm-coactivated CaYAl3O7 phosphor synthesized by using a combustion method - 余红玲 余雪 徐旭辉 姜庭明 杨鹏辉 焦清 周大成 邱建备 (中国物理B：英文版, 2013)
A novel red-emitting phosphor, CaYA1307： Eu^3＋, Sm^3＋, is synthesized by a combustion method at a low temperature （850 ℃）, and the single phase of CaYA1307 is confirmed by powder X-ray diffraction measurements. The photoluminescence property results reveal that the red emission intensity of Eu^3＋ is strongly dependent on the Sm^3＋ concentration. Only the Eu^3＋ luminescence is detected in the Eu^3＋-Sm^3＋ co-doped CaYA1307 phosphor with 393 nm excitation. However, under the characteristic excitation （402 nm） of Sm^3＋, not only the Sm^3＋ emission but also the Eu^3＋ emission are observed. A possible mechanism of the energy transfer between Sm^3＋ and Eu3＋ is investigated in detail.